2005
DOI: 10.1507/endocrj.52.207
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Thyroid Follicular Carcinoma by the Vascular Pattern and Velocimetric Parameters Using High Resolution Pulsed and Power Doppler Ultrasonography

Abstract: Abstract. The aim of this study was to define the preoperative diagnosis of thyroid follicular carcinoma by the vascular pattern and velocimetric parameters using high resolution pulsed and power Doppler ultrasonography (US). We compared the vascular pattern and the velocimetric parameters, such as peak systolic velocity (Vmax), end-diastolic velocity (Vmin), pulsatility index (PI), or resistance index (RI) between follicular adenoma (FA, n = 25) and follicular carcinoma (FC, n = 10) and analysed them by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 17 publications
3
45
1
2
Order By: Relevance
“…According to a study by Paramo et al, the incidence of malignancy in Fn increased if nodule size was larger than 4cm, this suggested larger nodules have a higher possibility of being malignant [10]. However, in our study FC were not found more frequently in nodules larger than 4cm; in fact, 8 (32%) cases of malignancy were found in nodules measuring less than ful in differentiating malignancy from benign FA [23].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…According to a study by Paramo et al, the incidence of malignancy in Fn increased if nodule size was larger than 4cm, this suggested larger nodules have a higher possibility of being malignant [10]. However, in our study FC were not found more frequently in nodules larger than 4cm; in fact, 8 (32%) cases of malignancy were found in nodules measuring less than ful in differentiating malignancy from benign FA [23].…”
Section: Discussioncontrasting
confidence: 72%
“…When compare to Fukunari study, the number of FC was less but our study was not only designed to evaluate the flow pattern of FN but to evaluate the uS features of Fn in detail including the internal content, margin, shape, echotexture, echogenicity, and the presence of calcifications with the pre-operative cytology results. As several authors suggested that Doppler flow analysis can provide useful information regarding the probability of malignant involvement with follicular cytology results [4,[22][23][24], we agree that it is useful in the decision-making process for surgical process, and the extent of resection of follicular lesions along with more careful pre-operative assessment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A larger size and increased intranodular vascularity on color or power Doppler imaging are also predictive of malignancy [109][110][111][112].…”
Section: Assessment and Treatment Of Thyroid Nodulesmentioning
confidence: 99%
“…Existem poucos estudos na literatura avaliando a utilização do Doppler pulsado, com medida do índice de resistência arterial, nos nódulos da tireoide, alguns com bons resultados (3,(26)(27)(28), principalmente na tentativa de diferenciação das neoplasias foliculares malignas no grupo citológico indeterminado. Outros estudos não encontraram utilidade para tal recurso (29,30).…”
Section: Resultsunclassified